2013
DOI: 10.1186/1472-684x-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the use of Levomepromazine for symptom control in the palliative care setting: a systematic review

Abstract: BackgroundLevomepromazine is an antipsychotic drug that is used clinically for a variety of distressing symptoms in palliative and end-of-life care. We undertook a systematic review based on the question “What is the published evidence for the use of levomepromazine in palliative symptom control?”.MethodsTo determine the level of evidence for the use of levomepromazine in palliative symptom control, and to discover gaps in evidence, relevant studies were identified using a detailed, multi-step search strategy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 68 publications
0
26
0
2
Order By: Relevance
“…Other prescription surveys have found decreasing utilization of first‐generation antipsychotic drugs . The prevalent use of first‐generation antipsychotic drugs, despite their higher risk of extrapyramidal side effects in comparison with second‐generation antipsychotic drugs, might be because of use in other medical specialties such as neurology, oncology and palliative care: for example, levomepromazine (methotrimeprazine) is used in the treatment of medication‐overuse headache as supportive treatment during detoxification and for nausea or delirium in palliative care . Haloperidol is recommended for the pharmacological intervention in delirium and nausea as part of palliative care and is, together with zuclopenthixol, recommended as third‐line treatment in schizophrenia in Denmark due to a lower risk of orthostasis and the related risk of falls in comparison with second‐generation antipsychotics, especially clozapine, quetiapine and risperidone .…”
Section: Discussionmentioning
confidence: 99%
“…Other prescription surveys have found decreasing utilization of first‐generation antipsychotic drugs . The prevalent use of first‐generation antipsychotic drugs, despite their higher risk of extrapyramidal side effects in comparison with second‐generation antipsychotic drugs, might be because of use in other medical specialties such as neurology, oncology and palliative care: for example, levomepromazine (methotrimeprazine) is used in the treatment of medication‐overuse headache as supportive treatment during detoxification and for nausea or delirium in palliative care . Haloperidol is recommended for the pharmacological intervention in delirium and nausea as part of palliative care and is, together with zuclopenthixol, recommended as third‐line treatment in schizophrenia in Denmark due to a lower risk of orthostasis and the related risk of falls in comparison with second‐generation antipsychotics, especially clozapine, quetiapine and risperidone .…”
Section: Discussionmentioning
confidence: 99%
“…48 Pharmacotherapies: Fifteen reviews were found synthesizing evidence on pharmacological interventions for pain, dyspnea, nausea/vomiting, and constipation, but evidence was low-to very low-quality, due to inconsistent findings across studies and a lack of pooled effect estimates. Eight reviews addressed pharmacological interventions for pain management and concluded there is limited evidence for metamizole in cancer pain, 70 methadone as a first-choice opioid for cancer pain, 76 levomepromazine for pain among palliative care patients, 89 paracetamol and morphine for pain in dementia patients, 65 and the use of bisphosphonates 68 or adjuvant analgesics 66 for relief of metastatic bone pain. One review concluded that transdermal buprenorphine and transdermal fentanyl demonstrate equivalent analgesic efficacy in patients with cancer pain but noted that long-term data are lacking, 56 and another review concluded that once-aday dexamethasone is the preferred corticosteroid for pain control among adult patients with glioma.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…129 Methotrimeprazine (levomepromazine), a phenothiazine, is often used in agitated delirium at the end of life, in which its sedative properties and subcutaneous route of administration are advantageous. 87,130,131 However, it is not available worldwide including in the United States.…”
Section: Resultsmentioning
confidence: 99%